2008
DOI: 10.1002/eji.200737889
|View full text |Cite
|
Sign up to set email alerts
|

Protective anti‐mycobacterial T cell responses through exquisite in vivo activation of vaccine‐targeted dendritic cells

Abstract: Vaccine efficacy largely depends upon DC targeting and activation. The most potent TLR soluble ligands induce diffuse DC activation, which may be associated with marked pro‐inflammatory responses and possibly adverse effects. This raises the concern that effective vaccine adjuvants may similarly rely on widespread DC activation. Using a promising candidate vaccine against tuberculosis (fusion protein of Ag85B and 6‐kDa early secretory antigenic target (ESAT‐6)) formulated in the potent IC31® adjuvant, DC targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 32 publications
2
35
0
Order By: Relevance
“…We have shown that alum-enhanced neonatal Ab response to meningococcal protein antigens, but serum bactericidal activity which is a surrogate for protective efficacy [36] was less enhanced than if Th-promoting adjuvants such as CpG-ODN or LT-K63 were given with the vaccine [37]. Recently, Siegrist et al [23] showed enhanced IFN-c production in mice receiving IC31 Ò , whereas alum only enhanced IL-5 production, which was in accordance with enhanced expression of co-stimulatory molecules and IL12-p40 of vaccineassociated DC by IC31 but not alum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that alum-enhanced neonatal Ab response to meningococcal protein antigens, but serum bactericidal activity which is a surrogate for protective efficacy [36] was less enhanced than if Th-promoting adjuvants such as CpG-ODN or LT-K63 were given with the vaccine [37]. Recently, Siegrist et al [23] showed enhanced IFN-c production in mice receiving IC31 Ò , whereas alum only enhanced IL-5 production, which was in accordance with enhanced expression of co-stimulatory molecules and IL12-p40 of vaccineassociated DC by IC31 but not alum.…”
Section: Discussionmentioning
confidence: 99%
“…Although KLK by itself induces a Th2-biased cytokine profile [19], IC31 Ò enhances a strong Th1 response detected by high interferon (IFN)-c levels [20][21][22] even in aged mice [22]. IC31 Ò elicits a potent but focused dendritic cell (DC) activation without triggering bystander proinflammatory responses [23]. Based on these results we expected that IC31 Ò could be a suitable adjuvant to enhance the weak neonatal immune responses and correct the Th2 bias.…”
Section: Introductionmentioning
confidence: 99%
“…Cell preparation, cell staining, and flow cytometry For T cell analysis, cells from the spleen or, as indicated, the draining LN (dLN) were obtained by homogenization, whereas for APC analysis, dLN were digested as previously described (22,24). The brachial and axillary LN were harvested after s.c. immunization at the scruff of the neck and the mediastinal LN after i.p.…”
Section: Ag Adjuvants and Immunizationmentioning
confidence: 99%
“…Cytokines were determined by ELISA (72-h stimulation, IFN-g, IL-5, IL-10, TNF-a, IL-17, TGF-b), ELISPOT assay (48-h simulation, IFN-g, IL-5), and intracellular cytokine staining by FACS (6-h stimulation, IFN-g, TNF-a, IL-2) as previously described (22,24).…”
Section: Assessment Of T Cell Responsesmentioning
confidence: 99%
“…The DCs subsequently drain to lymph nodes where they stimulate specific immunity. 10,11 Recent work in mice suggests protective immunity induced by H4-IC31 is highly sensitive to antigen dose, 12 while a clinical response to a similar vaccine was directly influenced by the adjuvant dose. 13 Understanding the functional relationship between the adjuvant and antigen is critical to define vaccine formulations.…”
mentioning
confidence: 99%